Geographical Information System (GIS) Mapping of Spatio-Temporal pollution status of Rivers in Ibadan, Nigeria (2008)
More accurate spatio-temporal predictions of urban environment arc needed as a basis for assessing exposures as a part of environmental studies and to inform urban protection policy and management. In this study, an information system was developed to manage die physico-chemical pollution information of Ibadan river system. Oyo Slate, Southwest Nigeria. The study took into account die seasonal influences of point and non-point discharges on die levels of physico-chemical parameters. The overall sensitivity of the watershed to physicochemical environmental pollution revealed dial during dry season, of the 22 (100%) sample points, only 3(13.6%) were unpolluted, 6 (27.3%) were slightly polluted, 10 (45.4%) were moderately polluted. 2 (91%) were seriously polluted and 1 (4.5%) was exceptionally polluted During rainy season, 3 (13.6%) were unpolluted. 7 (31.8%) were slightly polluted, 9 (40.9%) were moderately polluted, 2 (9.1%) were seriously polluted and 1 (4.5%) was exceptionally polluted There is a considerable environmental risk associated with the present level of pollution of the Ibadan river water body on fish health and biodiversity This research provides a basis for aquatic management and assist in policy making at national and international levels Appropriate strategies for the control of point and non-point pollution sources, amendments and enforcement of legislation should be developed.